Research of Premature Failure of Bench Fatigue Test of the Car Aluminum Housing Main Reducer - Zhao Wenhua; Li Kai; Wang Kai (Jixie chuandong)
In order to analyze premature failure of the car aluminum housing main reducer during the bench fatigue test,the test for measurement,the finite element numerical simulation and the dynamics simulation of the test process are carried out. The research is made on the main effective factors indicates the main cause for premature failure is that the jig is not fit for the aluminum housing. Then the corresponding improved of jig is varied out and the correctly is verified through tests. The technical requirements of the bench fatigue test jig of the car aluminum housing main reducer are proposed based the research results.